Экстракция технологических данных процессов разделения широкой фракции легких углеводородов и пропан-пропиленовой фракции - Ульев, Леонид Михайлович; Маатоук, А. (НТУ "ХПИ", 2015)
Потенциал энергосбережения в процессах стабилизации ППФ, разделения ППФ и разделения ШФЛУ, исследуется в данной работе. Определены все технологические потоки, которые необходимы для интеграции процессов. Для уточнения теплофизических данных потоков, построена компьютерная модель процесса в программе UniSim. На основании анализа технологической схемы, собраны теплофизические данные технологических потоков, которые систематизированы и занесены в потоковую таблицу.

The relevance of the topic due to the fact that rising energy prices encourages more efficient use of energy, as the level of energy consumption has a significant impact on the cost of finished products. Energy conservation is one of the most common concerns in gas separation plants. This article contains information about data extraction and heat integration of separation of light hydrocarbons plant. The pinch analysis method was selected to perform a reconstruction project. Technological streams that are needed for the integration process by using the pinch analysis method were identified. UniSim model of the studied process was created. Table for process stream data was compiled on the basis of these data. The data obtained will be used to further the process of reconstruction.
Data extraction for separation processes of light hydrocarbons
Keywords: энергосбережение; технологическая схема; пинч-анализ; легкие углеводороды; UniSim Design; technological plan; pinch-analysis; flowsheet